Predictive Factors of Lamivudine Treatment Success in a Hepatitis B Virus-Infected Pediatric Cohort: A 10-Year Study - Yasmine Yousef; Kathie Béland; Emmanuel Mas; Pascal Lapierre; Dorothée Bouron Dal Soglio; Fernando Alvarez (Canadian Journal of Gastroenterology)
BACKGROUND: Hepatitis B virus (HBV) infections are responsible for the development of chronic hepatitis in 400 million people worldwide. Currently, no consensus exists as to when treatment should be initiated for pediatric patients.